O zdrowy społeczny potencjał w organizacjach. Perspektywa integralna - Cenin, Mieczysław; Słowiński, Zdzisław (About healthy social potential in organizations : The integral perspective, 2006)
Coming out from the characteristic of a phenomenon known as ’Rat Race' the authors introduce its problem of the psychosomatic and social costs in the category of normality’s pathology so in other words the analytical social psychology. They propose to open the mutual area of social psychology and economics problems contemplation. Referring to the administration based on economic doctrines they find its original sources of insufficiency in the pathology of normality: in taking of the resources and single sided optimization of economic effects achieving. It shows the way leading to integral and global psychological and economic problems solution referring to an own formulated human science system concept kept in the frames of historical myth theory.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 328-336